Updating the NCTUns-6.0 tool to simulate parallel optical burst switching of all-optical ultra-dense WDM systems - Salih A.I.; Abdelouhahab A.; Mostafa S.A.; Zaiter M.J. (Kluwer Academic Publishers, 2023)
Dense wavelength division multiplexing; Optical communication; Optical switches; Simulators; Switching networks; Conventional techniques; Optical burst switching (OBS); Random wavelength assignment; Switching architectures; Switching technology; Ultra-dense WDM; Wavelength assignment; Wavelength division multiplexing networks; Optical burst switching